Distinctive chromosomal, mutational and transcriptional profiling in colon versus rectal cancers - Maria Teresa De Angelis; Antonia Rizzuto; Angela Amaddeo; Carlo Sagnelli; Niccolò Vono; Michela Reda; Valentina Lise; Luca Parrillo; Carmela De Marco; Donatella Malanga; Gianluca Santamaria; Giuseppe Viglietto (Journal of Translational Medicine)
Abstract Background Colorectal cancer (CRC) encompasses tumors arising in the colon (CC) and rectum (RC), often treated as a single disease despite emerging evidence of biological divergence. Understanding the molecular differences between CC and RC is critical for improving diagnosis, prognosis, and therapeutic strategies. Methods We performed an integrated genomic and transcriptomic analysis of CC and RC data from The Cancer Genome Atlas (TCGA) to investigate their degree of similarity and observed that these tumors present distinct molecular profiles, which suggest an evolution through divergent pathways. Comparative analyses included copy number alterations (CNAs), somatic mutations, driver gene prediction, differential gene expression, pathway enrichment, and survival analysis. Results Chromosomal analyses revealed that 43% of focal and 77% of large-scale CNAs were specific of CC, while 10.5% and 57% were specific of RC with 8% of mutant genes unique to CC and 0.18% to RC. CC and RC presented distinct profiles of gene mutations, with CC showing significantly higher tumor mutational burden (0.51 muts/Mb vs 0.28 muts/Mb in RC). Distinct mutational signatures were identified, with CC characterized by a higher frequency of PIK3CA, BRAF, and DNAH1 mutations, while RC showed enrichment for TP53 and NRAS mutations. Importantly, analysis of predicted non-canonical driver genes identified ACVR1B, LTBP4, SETD1A as CC-specific drivers and C4BPA, EHD1 as RC-specific drivers, underscoring divergent oncogenic mechanisms. However, the most substantial divergence was observed in transcriptomic profiling, with 56% and 33% of DEGs (in CC and RC, respectively) that were tumor-type specific. Notably, RC tumors segregated into two distinct transcriptional subtypes (Cluster 1 and Cluster 2), with Cluster 1 showed a more heterogeneous Consensus Molecular Subtypes (CMS) distribution, while Cluster 2 enriched in CMS4 (mesenchymal) and CMS3 (metabolic) consensus molecular subtypes. Accordingly, Gene Set Enrichment Analysis revealed CC-specific upregulation of Wnt, MYC, and mTOR signaling pathways, and RC-specific enrichment of GPCR and neuronal development pathways. On the other hand, pseudogene expression was significantly higher in CC, suggesting differential mechanisms of transcriptional dysregulation. Finally, we identified an RC-specific multigene survival signature as a prognostic model involving upregulation of C2CD4B, HSPD1P1, LINC01356, CBX3P9, GATA2-AS1 and downregulation of ATP5F1EP2, HSP90AB3P and SNRPFP1. Conclusions Collectively, our findings provide robust molecular evidence that CC and RC follow divergent oncogenic pathways, emphasizing the need for site-specific biomarker development and therapeutic targeting in colorectal cancer.